Intersonic Competence of Sheikh Hamza Yusuf Da'wah Video: An Acoustic Phonetic Study - Saadiah, Nur Khofifah (Samsara Institute Publisher, 2025)
Intersonic competence is important for analyzing the sounds produced by speakers. Not only in the realm of music and instruments, but this can also be analyzed for other utterances. One of the speeches that can be analyzed that the reseracher uses in this research is the delivery of da'wah ‘preaching’ by Sheikh Hamza Yusuf as a native English speaker with an American English accent. The researcher chooses one video of Sheikh Hamza Yusuf entitled The Quran from the instagram account in account name @cafe.ihsan who shares lots of da’wah ‘preaching’ videos from the Muslim scholars. PRAAT software is used to count and analyze the intonatin and the speed. This study aims to analyze the influences of using variative intonation, variative speed and rhythm, and the background of the accent and the dialect. Therefore, this article analyzes the three discussions of intersonic competence. The data shows the use of variative intonation by Sheikh Hamza Yusuf: fall, rise-fall, and fall-rise intonations are indicated in the result, variative speed and rhythm, and the background of accent and dialect influence the audiences’ understanding.